The Comparison of Verb Affixations Contrastive between Batak Toba and Indonesia Language - Cristy, Samuel Nugraha; Lubis, Fadda Helmi Attarmy; Chunliu, Liao (TALENTA Publisher, 2023)
This study aims to contrast the verbs affixation between Batak Toba and Indonesia language to find more clearly the similarities and differences between the two languages. The problem studied is the verb affixation between Batak Toba and Indonesia language. The research method used is descriptive qualitative, using observation and note-taking techniques. The method in this study uses advanced techniques in the form of note-taking techniques. The note-taking technique is used as a data collection technique. The note-taking technique involves using written language to note several forms relevant to research. This research used written data from books and various sources discussing Batak Toba's grammar.